2015
DOI: 10.1021/es506110w
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic Acid Promoted Alachlor Degradation in Fe(III)/H2O2 Fenton System

Abstract: In this study, we demonstrate that protocatechuic acid (PCA) can significantly promote the alachlor degradation in the Fe(III)/H2O2 Fenton oxidation system. It was found that the addition of protocatechuic acid could increase the alachlor degradation rate by 10 000 times in this Fenton oxidation system at pH = 3.6. This dramatic enhancement of alachlor degradation was attributed to the complexing and reduction abilities of protocatechuic ligand, which could form stable complexes with ferric ions to prevent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(78 citation statements)
references
References 47 publications
(62 reference statements)
1
77
0
Order By: Relevance
“…16,33 Furthermore, in addition to the operating conditions of a Fenton system, the effect of substances present in the natural environment and wastewaters on the catalytic efficiency is also a matter of great concern especially for the removal of pollutants from environmental samples. 34,37,38 In this direction, a recent study by Papoutsakis et al demonstrated the enhancement of both the dark and photo-assisted Fenton reaction by cork boiling wastewater. 37 For this scenario, understanding mechanistic aspects of treatment processes is considered fundamental.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,33 Furthermore, in addition to the operating conditions of a Fenton system, the effect of substances present in the natural environment and wastewaters on the catalytic efficiency is also a matter of great concern especially for the removal of pollutants from environmental samples. 34,37,38 In this direction, a recent study by Papoutsakis et al demonstrated the enhancement of both the dark and photo-assisted Fenton reaction by cork boiling wastewater. 37 For this scenario, understanding mechanistic aspects of treatment processes is considered fundamental.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the huge number of studies, the vast majority of the works presented in the literature focus on kinetic experiments while few works report long‐term experiments for pollutants degradation using the Fenton reaction . Furthermore, in addition to the operating conditions of a Fenton system, the effect of substances present in the natural environment and wastewaters on the catalytic efficiency is also a matter of great concern especially for the removal of pollutants from environmental samples . In this direction, a recent study by Papoutsakis et al .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Since chloroacetanilide herbicides are persistent and not readily biodegradable, their degradation by physico-chemical processes has been widely investigated. [11][12][13][14][15][16][17][18][19] Among these processes, the reductive dechlorination of chloroacetanilide herbicides seems to be particularly relevant since it is a selective and well-controlled process and it is likely to increase their biodegradability since chloro-groups are often responsible for the biorecalcitrance of substrates. 20 Most chlorinated molecules can be directly reduced on cathodes but at very cathodic potentials close to the reduction of water.…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis of nanoparticles has received attention due to its use of environment-friendly precursors for nanoparticles synthesis with many other advantages such as economic viability, ease of production, eco-friendly nature, avoiding the use of harmful chemicals, conditions of high temperature and pressure, and the expensive instruments required for physical and chemical methods. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Microorganisms have the ability to reduce heavy metal salts to metal nanoparticles with a narrow size distribution due to the presence of various reductase enzymes. 15 In a previous report, silver nanoparticles and PbS quantum dots were synthesized by Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%